Multiple secularities beyond the West: religion and modernity in the global age - Burchardt, Marian; Middell, Matthias; Wohlrab-Sahr, Monika (Religion and its others, 2015)
Questions of secularity and modernity have become globalized, but most studies still focus on the West. This volume breaks new ground by comparatively exploring developments in five areas of the world, some of which were hitherto situated at the margins of international scholarly discussions: Africa, the Arab World, East Asia, South Asia, and Central and Eastern Europe. It examines the historical pathways, cultural meanings, and global entanglements of secular formations
Keywords: Aufsatzsammlung; Öffentlichkeit; Ritual; Politik; Säkularismus; Religion